Modelo para realizar estudios de emplazamiento para instalaciones nucleares en Argentina - Alegría, José Luis; Dorado, Norberto; Lachica, Ángel; Maidana, Waldemar J. P.; Martínez, Jerónimo J. C.; Martínez, Manuel Fermín; Paganini, Camilo E.; Palacios, Elías; Torres Arroyo, José Guillermo; Toth, Karoly (Comisión Nacional de Energía Atómica; Argentina, 1976)
Fil: Alegría, José Luis Comisión Nacional de Energía Atómica; Argentina